Exploring the relationships among safety leadership, safety climate, psychological contract of safety, risk perception, safety compliance, and safety outcomes - Omidi, Leila; Karimi, Hossein; Pilbeam, Colin; Mousavi, Saeid; Moradi, Gholamreza (Frontiers in Public Health, 2023)
Recently, two types of safety compliance behaviors including deep compliance and surface compliance were differentiated. The current study aimed to investigate the relationships among safety leadership, safety climate, psychological contract of safety (PCS), risk perception, and deep compliance and surface compliance behavior of workers. In addition, the effects of both deep and surface compliance on safety outcomes were considered. Workers' perceptions in terms of safety leadership, safety climate, PCS, risk perception, deep compliance, and surface compliance were measured by appropriate questionnaires. Three questions were asked to measure undesired safety outcomes. Structural equation modeling and Spearman correlation coefficient were applied for examining the research model and relationships among variables. The results of the current study showed that deep compliance was positively predicted by safety leadership, safety climate, and PCS and negatively predicted by risk perception and undesired safety outcomes. Surface compliance was positively predicted by safety leadership and safety climate and negatively predicted by risk perception and undesired safety outcomes. Surface compliance is not significantly predicted by PCS. With regard to the adverse safety outcomes, the results showed that both deep and surface compliance were negatively associated with adverse safety outcomes, however, deep compliance had a stronger negative correlation with adverse safety outcomes than surface compliance.